Dhaka Stress Scale-Adult: A scale for assessing psychosocial stressors among adults - Mullick, Mohammad S. I.; Algin, Sultana; Islam, Monirul; Phillipson, Adrian; Nahar, Jhunu S.; Morshed, Nahid Mahjabin; Chowdhury, Hafizur Rahman; Shahid, Selina Fatema Binte (Bangabandhu Sheikh Mujib Medical University Journal, 2019)
Stress is an integral part of daily life and inevitable. This study was aimed to produce a culturally validated scale for measuring stressful life events of adults in Bangladesh and formulate the relative life change units of each event. The study used qualitative research, including a focus group and questionnaire, as well as quantitative statistical analysis in the validation process. Researchers first developed a provisional scale with 62 items that were translated in Bangla through a translation exercise. Using an open-ended question along with this provisional scale on 518 (260 rated on imagination and 258 on experience) subjects, researchers developed Dhaka Stress Scale-Adult with 58 items and the predictive interpretation of the overall score was made. Content validity was found excellent as I-CVI was 1 except 3 items and S-CVI was 0.91. In factor analysis on the two-factor model, no item had salient loading on more than one factor and there were 3 items failed to load on either factor. The correlation coefficient was 0.84 between this scale and the Presumptive Stressful Life Events Scale. In term of reliability, Cronbach’s alpha values were ranging from 0.53-0.88. The scale is simple to administer to assess stress and usable for both clinical and research purpose.